Effect of Superdisintegrant Concentration on the Physical Properties of Diclofenac Sodium Orally Disintegrating Granules (ODGs) - Bangkit Riska Permata; Indari Rahimi; Danang Raharjo; Iqbal Wahid Abdullah (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
The development of diclofenac sodium orally disintegrating granules (ODGs) offers a promising approach to improve patient compliance, particularly among pediatric, geriatric, and dysphagic patients. Although crospovidone and sodium starch glycolate (SSG) are widely used as superdisintegrants, limited information is available regarding their optimal combination in diclofenac sodium ODG formulations. This study aimed to optimize the combination of crospovidone and SSG by evaluating different crospovidone ratios (2.4:1–1:2), including an equal ratio (1:1), on the physical characteristics and disintegration performance of diclofenac sodium ODGs prepared by wet granulation. Six formulations were developed while maintaining constant concentrations of other excipients. The granules were evaluated for flow properties, particle size distribution, bulk and tapped density, Carr’s Index, Hausner’s ratio, moisture content, and disintegration time. Statistical analysis was performed using one-way ANOVA (α = 0.05). All formulations exhibited excellent flowability, with angles of repose of 18.10–19.45°, Carr’s Index of 12.28–13.46%, Hausner’s ratio of 1.14–1.16, moisture content of 2.41–2.73%, and uniform particle size distribution (d50: 305–325 µm). All formulations complied with the European Pharmacopoeia disintegration requirement (<180 s), while F1, F2, and F4 also met the USP criterion (<30 s). Disintegration time ranged from 21.38 to 38.47 s and was significantly affected by the crospovidone–SSG ratio (p < 0.05). Formulation F4 demonstrated the fastest disintegration time (21.38 s) and the most favorable overall characteristics. These findings indicate that optimizing the crospovidone-SSG combination enhances disintegration performance while maintaining acceptable physical quality, making F4 a promising diclofenac sodium ODG formulation.